Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1
\(\left(x-2\right):2.3=6\)
\(\Leftrightarrow\left(x-2\right):2=2\)
\(\Leftrightarrow\left(x-2\right)=4\)
\(\Leftrightarrow x=4+2=6\)
c) ta có
\(\left[\left(2x+1\right)+1\right]m:2=625\)
\(\Leftrightarrow\left[\left(2x+1\right)+1\right]\left\{\left[\left(2x+1\right)-1\right]:2+1\right\}=1250\)
\(\Leftrightarrow\left(2x+1\right)^2+1-1:2+1=1250\)
\(\Leftrightarrow\left(2x+1\right)^2+1-2+1=1250\)
\(\Leftrightarrow\left(2x+1\right)^2+1-2=1249\)
\(\Leftrightarrow\left(2x+1\right)^2+1=1251\)
\(\Leftrightarrow\left(2x+1\right)^2=1250\)
...
2
\(\left(x-\frac{1}{2}\right).\frac{5}{3}=\frac{7}{4}-\frac{1}{2}\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right).\frac{5}{3}=\frac{5}{4}\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right)=\frac{5}{4}:\frac{5}{3}\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right)=\frac{5}{4}.\frac{3}{5}\)
\(\Leftrightarrow x-\frac{1}{2}=\frac{3}{4}\)
\(\Leftrightarrow x=\frac{3}{4}+\frac{1}{2}=\frac{5}{4}\)
a: \(\Leftrightarrow\left(\dfrac{13}{4}:x\right)\cdot\left(-\dfrac{5}{4}\right)=\dfrac{-10}{6}-\dfrac{5}{6}=\dfrac{-15}{6}=\dfrac{-5}{2}\)
\(\Leftrightarrow\dfrac{13}{4}:x=\dfrac{5}{2}\cdot\dfrac{5}{4}=\dfrac{25}{8}\)
hay \(x=\dfrac{13}{4}:\dfrac{25}{8}=\dfrac{13}{4}\cdot\dfrac{8}{25}=\dfrac{26}{25}\)
b: \(\Leftrightarrow\dfrac{3}{4}:x=\dfrac{11}{36}-\dfrac{1}{4}=\dfrac{2}{36}=\dfrac{1}{18}\)
=>\(x=\dfrac{3}{4}:\dfrac{1}{18}=\dfrac{54}{4}=\dfrac{27}{2}\)
c: \(\Leftrightarrow\left(-\dfrac{6}{5}+x\right):\left(-3.6\right)=-\dfrac{7}{4}+\dfrac{1}{4}\cdot8=\dfrac{1}{4}\)
=>x-6/5=-9/10
=>x=3/10
a) 2/3x +1/2 = 1/10
=> 2/3x = 1/10 - 1/2
2/3x = -2/5
=> x = -2/5 : 2/3
x = -3/5
b) (4,5 - 2x) : 3/4 = \(1\frac{1}{3}=\frac{4}{3}\)
=> 4,5 - 2x = 4/3 x 3/4
4,5 - 2x = 1
-2x = 4,5 - 1
-2x = 3,5
=> x = 3,5 : (-2)
x = - 1,75
c) x/4 = 5/20
=> x = 5/20 x 4
x = 1
d) ?????
2/3x+1/2=1/10
<=>2/3x=1/10-1/2
<=>2/3x=-2/10
=>x=-2/10 chia 2/3=-3/10
ý kia tương tự
\(a,\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
\(\Rightarrow\frac{1}{2}x+\frac{3}{5}x-\frac{6}{5}=3\)
\(\Rightarrow x\left(\frac{1}{2}+\frac{3}{5}\right)=3+\frac{6}{5}\)
\(\Rightarrow\frac{11}{10}x=\frac{21}{5}\)
\(\Rightarrow x=\frac{21}{5}:\frac{11}{10}\)
\(\Rightarrow x=\frac{42}{11}\)
\(b,\left(3\frac{1}{2}-x\right).1\frac{1}{4}=-1\frac{1}{20}\)
\(\Rightarrow\left(\frac{7}{2}-x\right)\cdot\frac{5}{4}=-\frac{21}{20}\)
\(\Rightarrow\frac{7}{2}-x=-\frac{21}{20}:\frac{5}{4}\)
\(\Rightarrow\frac{7}{2}-x=-\frac{21}{25}\)
\(\Rightarrow x=\frac{7}{2}--\frac{21}{25}\)
\(\Rightarrow x=\frac{7}{2}+\frac{21}{25}\)
\(\Rightarrow x=\frac{217}{50}\)
a) \(x+\frac{1}{2}\cdot\frac{1}{3}=\frac{3}{4}\)
\(x+\frac{1}{6}=\frac{3}{4}\)
\(x=\frac{3}{4}-\frac{1}{6}\)
\(x=\frac{7}{12}\)
Vậy \(x=\frac{7}{12}\).
b) \(x+2\frac{3}{4}=5\frac{2}{3}\)
\(x+\frac{11}{4}=\frac{17}{3}\)
\(x=\frac{17}{3}-\frac{11}{4}\)
\(x=\frac{35}{12}\)
Vậy \(x=\frac{35}{12}\).
a, x + \(\frac{1}{2}.\frac{1}{3}=\frac{3}{4}\)
X + \(\frac{1}{6}=\frac{3}{4}\)
X = \(\frac{3}{4}-\frac{1}{6}\)
X = \(\frac{7}{12}\)
b, x + \(2\frac{3}{4}\)= \(5\frac{2}{3}\)
X + \(\frac{11}{4}=\frac{17}{3}\)
X = \(\frac{17}{3}-\frac{11}{4}\)
X = \(\frac{35}{12}\)
\(a,\left|4-x\right|=10\)
\(\Rightarrow4-x=10\text{ hoặc }4-x=-10\)
\(x=4-10\) \(x=4-\left(-10\right)\)
\(x=-6\) \(x=4+10\)
\(x=14\)
\(\text{Vậy }x=-6;x=14\)
\(b,\frac{4}{5}-x=1\frac{1}{2}\)
\(\frac{4}{5}-x=\frac{3}{2}\)
\(x=\frac{4}{5}-\frac{3}{2}\)
\(x=\frac{8}{10}-\frac{15}{10}\)
\(x=-\frac{7}{10}\)
a, |4-x|=10
TH1: 4-x=10
x=4-10
x=-6
Th2:4-x=-10
x=4-(-10)
x= 14
b,4/5-x=1 1/2
4/5-x=3/2
x= 4/5-3/2
x=-7/10